An Analysis of the Live on Board Phenomenon as a Form of Marine Tourism Development in Labuan Bajo, Indonesia - Dewi Sartika Umul; Andriano Calrinto Mami; Yohana Etheldreda Ine Dae (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study analyzes the phenomenon of live on-board tourism as a form of marine tourism development in Labuan Bajo, Indonesia, with particular attention to its characteristics and driving factors. Employing a qualitative phenomenological approach, the research explores how liveaboard tourism has evolved into a distinctive marine-based tourism model through the interaction of destination attributes and stakeholder motivations. Data were collected through in-depth interviews with three key informant groups: maritime regulators (KSOP), liveaboard vessel operators, and tourists. The findings reveal that liveaboard tourism in Labuan Bajo is characterized by an integrated tourism system that combines transportation, accommodation, and continuous marine experiences within a single travel product. Its development is driven by strong pull factors, including exceptional marine landscapes, immersive experiential value, and digitally mediated destination imagery, as well as push factors stemming from tourists’ psychological needs and the entrepreneurial responses of local operators. Triangulation across informant groups confirms the consistency and validity of these findings. This study contributes to tourism motivation literature by contextualizing push–pull dynamics within marine experiential tourism and offers insights for the sustainable governance of liveaboard tourism destinations.